Child-to-parental violence and empathy in Peruvian adolescents - Candela Ayllón, Víctor Eduardo (2019)
The purpose of this study was to determine the concomitance of child-parent violence and adolescent empathy in the district of Imperial in the Province of Cañete, Lima, 2018. This was an investigation carried out under a basic quantitative method of descriptive comparative type with correlational scope and also under the design guidelines of a non-experimental design where the measurements took place at specific points in time (cross-sectional data). The sample consisted of 354 adolescents who were selected by an intentional non-probabilistic sampling. The were applied the Child-to-Parent Aggression Questionnaire (CPAQ) proposed by Calvete et al. (2013); the Toronto Empathy Questionnaire (Spreng et al., 2009; cited by Nolasco, 2012) to measure empathy; and the Davis scale (1983), which assesses cognitive aspects of empathy. The relationship between variables was established by determining patterns of behaviour whose contents have marked behavioral traits in both the child-parent violence and the adolescent empathy, a thing that permitted the study to obtain a resultant of four different clusters that explain the relationship between the variables of study